Abdominal compartment syndrome in severe acute pancreatitis (review of literature) - L. A. Otdelnov; A. S. Mukhin (Вестник хирургии имени И.И. Грекова)
The study was performed for analysis of current understanding of intra-abdominal hypertension and abdominal compartment syndrome in patients with severe acute pancreatitis.The English and Russian articles about intra-abdominal hypertension and abdominal compartment syndrome in patients with severe acute pancreatitis were analyzed. The articles were found in «Russian Science Citation Index» and «PubMed».There is a pathogenetic relationship between increased intra-abdominal pressure and the development of severe acute pancreatitis.For today, it was shown that intra-abdominal hypertension in patients with severe acute pancreatitis is associated with significantly higher APACHE-II and MODS score, prevalence of pancreatic and peripancreatic tissue lesions, early infection of pancreatic necrosis and higher mortality.The article considers various variants of decompressive interventions such as decompressive laparotomy, fasciotomy and percutaneous catheter drainage. For today, there are no randomized studies devoted to researching effectiveness of different decompressive interventions.The study showed that it is necessary to regularly monitor intra-abdominal pressure in patients with severe acute pancreatitis. Patients with intra-abdominal hypertension require emergency medical management to reduce intra-abdominal pressure. Inefficiency of the medical management and development of abdominal compartment syndrome are indications for surgery. The effectiveness of different decompressive interventions requires further studies.